PERLINDUNGAN HAK ANAK AKIBAT KEKERASAN SEKSUAL DI PONDOK PESANTREN PERPSEKTIF MAQASHID SYARIAH (YASSER AUDA) DAN HUKUM POSITIF - Herawati, Netti; Abnan Pancasilawati; Maisyarah Rahmi (The Juris, 2023)
This research discusses protecting children's rights in the context of sexual violence in boarding schools, using the perspective of Maqoshid Syariah presented by Yasser Auda and integrating it with positive law. The research aims to analyze the relevance of the concepts of Maqoshid Syariah in protecting the rights of children who are victims of sexual violence, as well as comparing it to positive law. This research uses a phenomenological approach and literature analysis methods by referring to Yasser Auda's works on Maqoshid Syariah and positive legal studies on protecting children's rights and sexual violence in boarding schools. The research results show that; First, The background of the perpetrator, who is the Leader of the Islamic Boarding School, is only due to lust and conscious will by forcing the victim to marry ‘Sirri’ without the knowledge of other people; second, The form of legal protection given to victims of sexual violence is legally processed, providing health protection in the form of mental health through UPT Integrated Service Center for Empowerment of Women and Children (P2TP2A) Kutai Kartanegara, and offer legal assistance to victims to be accompanied, third, must include the role of religion, protect the victim's soul both physically and non-physically (mentally), provide guarantees for a good education, offspring obtained from marriage based on an agreement, protection in socio-economic terms, protection in the form of clearing the victim's good name.